Perceptual for enrolled and not enrolled the puplis in kindergartens (comparative study) (Journal Of Educational and Psychological Researches, 2022)
Enrollment in kindergarten child accomplishes many positive aspects, that’s what Im sure a lot of modern educational trends in child education preschool in the importance of exposing children to a variety of sensory stimuli that contribute to impart a range of sound concepts.Current research aims to know:1.the level of sensory perception in the first primary grade students a sample search.2.differences in perception of elementary first-graders with variable gender male, female))   3.differences in perception of the first primary grade students attending and not attending kindergarten in accordance with variable attendance (attending, not attending).school students (first grade) from attending and not attending kindergartens, the cognitive abilities test researcher embraced the sensual lhiod (M. K. Haywood1986) after adapted and adjusted appropriately on a sample Search and make sure a handout and the stability data were analyzed using statistical pouch (spss) the researcher has the following results:1.first grade students found enrolled in kindergartens have cognitive abilities that may be due to sensory methods, teaching methods and curricula of kindergartens include learning experiences and activities exercised by the child itself through the use of senses (self). .2.the important role of stage (kindergartens) and its educational programs and activities in different aspects of growth in this dynamic sense side aspects.It also developed a number of recommendations including:1.to encourage families to send their children to kindergarten because they targeted educational stage at least as important as the rest of the stages as the basis for subsequent phases. 2.strengthening the curriculum, particularly in the first primary grade classroom activities and non-descriptive to develop sensory and mental abilities in children.And a number of proposals, including:1.other studies dealing with perceptual relationship to other variables, not covered in this research, as a failure of knowledge and independence.2.other studies similar to current research on different social strata, other age stages and results of those studies compared with the current search results.